2022
DOI: 10.1093/nar/gkac815
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of flagellar motility regulation by the MogR repressor and the GmaR antirepressor in Listeria monocytogenes

Abstract: The pathogenic Listeria monocytogenes bacterium produces the flagellum as a locomotive organelle at or below 30°C outside the host, but it halts flagellar expression at 37°C inside the human host to evade the flagellum-induced immune response. Listeria monocytogenes GmaR is a thermosensor protein that coordinates flagellar expression by binding the master transcriptional repressor of flagellar genes (MogR) in a temperature-responsive manner. To understand the regulatory mechanism whereby GmaR exerts the antire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Here, target prediction analyses revealed that Rli82 was capable of complementary pairing with bases at the positions -22 to -8 in the 5'-UTR of flaA mRNA, a site possibly representing the ribosomal binding site (RBS). Furthermore, the motility of the LM-∆Rli82 strain was significantly enhanced, which was in agreement with the observation of more flagella in It has been proven that the functioning of LM flagella is restricted to temperatures below 37°C due to the opposing activities of the MogR transcriptional repressor and the GmaR anti-repressor (13,(30)(31)(32). Once LM enters the host, however, the biosynthesis of flagella is suppressed to help the bacterium evade the host's immune system, thereby facilitating its survival and proliferation in vivo (31).…”
Section: Discussionsupporting
confidence: 87%
“…Here, target prediction analyses revealed that Rli82 was capable of complementary pairing with bases at the positions -22 to -8 in the 5'-UTR of flaA mRNA, a site possibly representing the ribosomal binding site (RBS). Furthermore, the motility of the LM-∆Rli82 strain was significantly enhanced, which was in agreement with the observation of more flagella in It has been proven that the functioning of LM flagella is restricted to temperatures below 37°C due to the opposing activities of the MogR transcriptional repressor and the GmaR anti-repressor (13,(30)(31)(32). Once LM enters the host, however, the biosynthesis of flagella is suppressed to help the bacterium evade the host's immune system, thereby facilitating its survival and proliferation in vivo (31).…”
Section: Discussionsupporting
confidence: 87%
“…Unfortunately, we could not predict the complex structure with a high confidence score, possibly indicating the existence of multiple binding modes. Besides its enzymatic function, GmaR’s C-terminal domain also acts as a transcriptional regulator through interaction with the MogR repressor. , However, the potential for a comparable dual role in FlgGT1’s CTD is difficult to assess due to the lack of a MogR homologue in the P. alvei genome.…”
Section: Resultsmentioning
confidence: 99%
“…Besides its enzymatic function, GmaR's C-terminal domain also acts as a transcriptional regulator through interaction with the MogR repressor. 21,30 However, the potential for a comparable dual role in FlgGT1's CTD is difficult to assess due to the lack of a MogR homologue in the P. alvei genome.…”
Section: ■ Introductionmentioning
confidence: 99%
“…jejuni (ATCC 33291) as a DNA template with DNA primers containing the recognition sequence of the BamHI or SalI restriction enzyme at one end. The PCR product was treated with the BamHI and SalI restriction enzymes and was ligated using T4 DNA ligase into a pET49b plasmid variant that was designed to express RecR protein in fusion with an N-terminal hexahistidine tag and a subsequent thrombin cleavage sequence [ 19 ]. The nucleotide sequence of the insert in the cjRecR expression plasmid was confirmed using DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%